PENINGKATAN MINAT BELAJAR BAHASA INGGRIS ANAK USIA DINI - Chamelya Vivi Crystanty Sene; Antonia Tefa; Beatrix Purnama Sari; Nilson F. Ndolu (LPPM Universitas Bina Bangsa, 2023)
The benefit of this activity is to encourage children to learn English from an early age. This activity was held at the Sonaf Maneka Orphanage as a partner of this activity. This activity is carried out through two methods: providing theory and providing direct teaching practice carried out by the PKM team. By using media such as songs, videos, pictures, and games. The material provided includes the alphabet, colors, body parts, numbers, and animals. Apart from that, to avoid boredom for recipients of the material, several games, such as word games, are also provided. This activity is considered to have a positive impact and foster children's interest in learning English, as shown by the children's enthusiastic responses. In addition, the children began repeating the English words they learned, such as the names of colors and numbers, on the last day of service. This is consistent with the idea that children have the ability to imitate what they see and hear. Therefore, we can conclude that this activity successfully achieved its aim of fostering children's interest in learning English